Ossification of posterior atlantoaxial membrane causing spinal stenosis – A case report - Yen-Ting Liu; Chon-Haw Tsai; Po-Hao Huang; Po-Chang Wu (Heliyon, 2023)
Background: Ossification of the posterior atlantoaxial membrane (PAAM) is a rare cause of spinal cord compression. Case presentation: A 46-year-old woman with rheumatoid arthritis (RA) and a 2-year history of slowly progressive gait disturbance underwent surgery for right knee stiffness and right lower limb mild weakness. A neurologic examination revealed brisk deep tendon reflexes (DTR) and spasticity in her four limbs. A computed tomography (CT) scan revealed spinal stenosis caused by ossification of the PAAM, a rare cause of spinal cord compression. The patient's lower limbs weakness and walking capability were ameliorated post-surgery. Conclusions: Although the exact mechanism of ossification of PAAM remains unclear, chronic mechanical stress as well as persistent atlantoaxial instability may promote the development of the ossification.